CONTRIBUTORS TO SCHEDULE DELAYS IN PUBLIC CONSTRUCTION PROJECTS IN SAUDI ARABIA: OWNERS’ PERSPECTIVE - Ibrahim Mahamid (Journal of Construction Project Management and Innovation)
This study aims at identifying the contributors to delays in public construction projects in Saudi Arabia from owners’ viewpoint. To do so, 22 public owners of construction projects completed a structured questionnaire survey. 35 factors were identified through literature review. The results indicated that the top delay contributors are: bid award for lowest price, poor site management, poor communication and coordination between construction parties, payments delay, poor labor productivity, and rework. These findings can support the Government in improving the regulations to meet the construction market needs, owners in planning and designing and evaluating policy, contractors and managers in planning and taking external and internal risks when costing and scheduling contracts, consultants in applying comprehensive contract information, and workers in conducting their day-to-day activities. Results will fill an important research and practice gap and help in improving time performance in public construction projects in Saudi Arabia and other developing countries.